Odpowiedź :
Odpowiedź:
a) 9x + 7 = 3x - 11 | - 3x
6x + 7 = -11 | - 7
6x = - 18 | : 6
x = - 3
b) 2x + 7 = 29 - 2x | + 2x
4x + 7 = 29 | - 7
4x = 22 | :4
x = 5,5
c) 3 - 7x = 4x - 19 | + 7x
3 = 11x - 19 | + 19
22 = 11x | : 11
x = 2
d) 5x + 7 = 3x + 18 | - 3x
2x + 7 = 18 | - 7
2x = 11 | : 2
x = 5,5
e) 6x - 15 = 3x - 9 | - 3x
3x - 15 = -9 | + 15
3x = 6 | :3
x = 2
f) 2 ( x + 6 ) = 28 - x
2x + 12 = 28 - x | + x
3x + 12 = 28 | - 12
3x = 16 | : 3
x = 5 i 1/3 ( czyli 5,(3) )
g) 12x - 7 = 3x + 20 | - 3x
9x - 7 = 20 | + 7
9x = 27 | : 9
x = 3
h) 2 ( x + 2 ) = 5 ( x - 1 )
2x + 4 = 5x - 5 | - 2x
4 = 3x - 5 | + 5
9 = 3x | : 3
x = 3
i) 3x - 2 = 11x + 20 | - 3x
- 2 = 8x + 20 | - 20
- 22 = 8x | : 8
x = - 2 i 3/4 ( czyli - 2,75)